Optimisation of monitoring using camera-traps and field evidence when identifying Eurasian otter Lutra lutra resting or breeding sites - Findlay, Melanie (Edinburgh Napier University, 2021)
The Eurasian otter Lutra lutra and its resting places are protected by EU and UK legislation. Consultant ecologists must identify resting sites so they can be protected during developments. Currently, consultants usually use field-signs, but radio-telemetry studies indicate this may be unreliable. Camera-traps could be used to identify resting sites within the consultancy industry. This research aims to improve field-sign and camera-trap survey methods to identify otter resting sites. Firstly, camera-trap methodology is considered. Arrays of camera-traps were used with continuous CCTV as a control so the effect of variables on detection success of mammal passes could be modelled. A six-year camera-trap study of an active breeding and resting site was analysed to optimise set-up. Distance from the camera-trap had a negative effect on trigger probability but a positive effect on registration probability (i.e. the probability that an image or video is captured given a trigger). Slower animals had greater trigger and registration probabilities while otters had reduced detection after immersion in water. A reduction of video clip duration, and exclusion of daytime monitoring would have reduced the amount of time watching video footage with minimal data loss. These findings guided a camera-trap study of 26 potential resting sites where field evidence was recorded at 21-day intervals. The camera-trap data was also used to identify rests and any relationships between resting and field evidence were investigated. A rest could only be observed on CT footage and was defined as an otter being within a structure for ≥ 15min. According to this criteria, six of the 26 sites were resting sites, with 95% of rests occurring in winter and spring. Latrines were exclusive to resting sites, and presence of bedding material was strongly related to resting sites. Data simulations calculated that a period of 35 days of camera-trapping in winter, repeated in spring would have a 95% probability of detecting a rest. These findings contribute to the evidence-base for guidelines for ecologists to identify resting sites as required by law. The patterns of otter activity, behaviour and field-signs provide a comparison for further studies. The research focusses on otter, but the approaches and principles could be applied more widely.